Transferência de cuidado realizada pelos profissionais de saúde em um serviço de urgência e emergência - Clayton Lima Melo (2019)
The transference of care (handoff or handover) consists in temporarily or permanentlytransferring the responsibility of the patient care to another person or group ofprofessionals. The objective of this study was to analyze the transfer of patient care inthe daily life of healthcare professionals of an emergency room and its influence on thequality of care. This is a case study of a qualitative nature, referenced on the daily lifeof Michel de Certeau's, especially regarding the concepts of tactics and strategy. Weconducted the study in an emergency room of a large public hospital, located in themunicipality of Belo Horizonte, Minas Gerais, Brazil. Thirty professionals of theemergency room among physicians, nurses, nursing technicians, stretcher bearer,social workers, psychologists, and dental surgeons (PS) directly involved in thetransfer of patient care partook of the study. We collected the data through individualinterviews using a semi-structured script, observation, and documentary analysis. Weused the data saturation criterion to close the interviews recorded, transcribed, andsubmitted to the Thematic Content Analysis. The data collection occurred after theapproval of the project by the Ethics Committee of the UFMG (COEP/UFMG) and theCommittee of Ethics and Research of the hospital under the decision no 1,519,784 and1,559,717, respectively. The participants signed the Term of Free and ClarifiedConsent (TFCC). The results were organized in five thematic categories:"Understanding the perspective of the professionals of an emergency room on thetransfer of patient care: multiple perspectives"; "Effective communication: strategiesand tactics experienced in the daily life of the professionals"; "Factors that interfere inteamwork and communication during a handover"; "Teamwork in the daily life of theprofessionals and reflexes on the handover"; "Care centered on the patient and family".The data revealed aspects of the daily life of the ER, as well as the profile of theinterviewees, subjects who, besides the established norms, use tactics to overcomedifficulties and show commitment to the assistance. The handover is understood indifferent ways by the professionals and is more closely connected to the transfer ofinformation. However, there is also a concern for the transfer of responsibilities andcare continuity. We identified strategies to define the flow of care and standardize thehandover, highlighting the Manchester protocol, electronic medical record, Situation-Background-Assessment-Recommendation (SBAR), and passometer, as well astactics (the real acting) revealed by the professionals. Mild skills such as assertiveness,listening, and negotiation are shown as tactics to increase the effectiveness ofcommunication. The nurse appears as a critical piece for the work of the multiprofessionalteam and handover organization. We identified factors related to theenvironment, structure, processes, and individuals that interfere in the communicationand teamwork during the handover. Teamwork in the ER is perceived more as agrouping than integration, impairing the handover. Care is performed according to thestandards and definitions of the professionals based more on the hospital´s reality andless on the needs of the patients and their family, which compromises patient handoverand the safety of this setting. Keywords: Patient Responsibility Transfer. Patient CareTeam. Emergency Medical Services. Patient safety.